Peran Dan Upaya KUA Kecamatan Jombang Terhadap Penyelesaian Permasalahan Wali Adhal Dalam Pernikahan - Maulidiyah, Dina; Muhammad (Universitas Hasyim Asy'ari (UNHASY) Tebuireng Jombang, 2024)
Abstract- This research want to show and describe about the role and efforts of KUA in the process of resolving the guardian adhal case. To find about the analysis the problems of murrasa is towards the role and efforts made by the KUA the progress of resolving the guardian adhal problem. This research is about qualitative field research with the descriptive-qualitative approach. In obtaining data, the author used the three data collection techniques, the interviews, observation and documentation. The author uses data analysis techniques from the data have taken, then analyzed using the maslahah mursalah theory. All of the research made the conclusion from the general research is that in implementing the role and efforts made by the KUA, the KUA plays a very big role in resolving problems, where the KUA uses methods by making the best efforts to reconcile the two parties who have problems with the guardian of adhal, with a process of tabayyun, by the parties. The KUA, visited the residence, provided understanding to both parties in the form of advice, and resolved the problems that occurred, where the efforts and roles carried out by the KUA were considered good and beneficial in dzhairiyah and spiritual terms, if viewed from the maslahah mursalah analysis. Keyword: The role, Efforts, Marriage, Resolving Adhal, Problems.